Much ado about Islam: The political integration of Muslim minorities in Guyana and Suriname - Aline-Sophia Hirseland (German Institute of Global and Area Studies (GIGA), 2024)
Differently to large parts of the scholarship assessing the impact of religion on the integration of Muslim minorities in Europe, the case selection employed in the present study allows for controlling relevant sociodemographic variables, namely migration background or rather generation and nationality or rather ethnicity. In contrast to the findings of a number of previous studies, this article's results increase doubts regarding the explanatory power here of "Islamic faith" and largely suggest a null finding hereon. Its findings show that alternative variables have significant effects on Muslim integration, such as generation, ethnicity, religiosity, gender, education, and age. Hence, adherence to the Islam turns out to be a weak predictor here. However, it is to be noted that significant effects for adherence to the Islamic faith were found for individual items composing the index on democratic values, though these findings don't appear to follow a homogenous pattern.
Keywords: 300; Guyana; Suriname; political integration; Muslim integration; Muslim minorities